(untitled) (Scientific journal of the Fergana State University, 2023)
Nanophases and films of SiO2 and metal silicides have been obtained by low-energy (Eo=1-5 keV) implantation of O2+, Ba+, Cu+ and Co+ ions and the by annealing of a free Si/Cu (100) nanofilm systems on the surface. Their surface morphology, composition, energy band parameters, maximum values of the secondary electron emission coefficient, and the quantum yield of photoelectrons have been determined. In particular, it has been shown that the band gap of metal silicides is 0.3-0.4 eV and their specific resistance is 100-500 mkOm×cm.